Lamin-B1 is a senescence-associated biomarker in clear-cell renal cell carcinoma - Radspieler, Melissa Marie; Schindeldecker, Mario; Stenzel, Philipp J.; Försch, Sebastian; Tagscherer, Katrin; Herpel, Esther; Hohenfellner, Markus; Hatiboglu, Gencay; Roth, Wilfried; Macher-Göppinger, Stephan (Oncology letters, 2019)
Clear-cell renal cell carcinoma (ccRCC) is a von-Hippel-Lindau gene (VHL) associated tumor disease. In addition to activating the hypoxia inducible factor (HIF) dependent oxygen-sensing pathway, VHL loss also has an impact on a HIF-independent senescence program which functions as a tumorigenesis barrier. Lamin-B1 is a nuclear intermediate filament protein that exhibits effects on chromatin structure and gene expression and acts as a senescence effector. In the present study, the expression and prognostic relevance of Lamin-B1 in a large cohort of ccRCC patients was examined and the report presents initial functional data on possible therapeutic implications. The expression of Lamin-B1 was measured by immunohistochemistry using a tissue microarray containing tumor tissue samples from 763 ccRCC patients. Chi-squared tests, Kaplan-Meier curves and Cox regression models were used to investigate the possible association between Lamin-B1 expression, clinical and pathological characteristics and patient survival. High Lamin-B1 expression was associated with poor clinical outcomes and multivariate Cox regression analyses revealed that Lamin-B1 was an independent prognostic factor for cancer-specific survival. Furthermore in vitro data suggested that Lamin-B1 acted as a functional downstream senescence effector in RCC cell lines. In conclusion, patients affected by ccRCC with high Lamin-B1 expression exhibit poor prognosis. Lamin-B1 may serve as a tissue-based biomarker for new therapeutic agents targeting therapy-induced senescence.
Gesehen am 05.03.2020